ANALYSIS OF MARKETING MANAGEMENT STRATEGY : A CASE STUDY OF RADEVA GROUP - Kusuma Wardhani, Fitra Wahyu; Rachmad Hidayat (Ekomania, 2024)
This research analyzes the marketing management strategy implemented by Radeva Group, a company engaged in the Food & Beverage (F&B) sector in Surabaya. Using a descriptive qualitative method, this research examines various aspects that influence the success of the company's marketing strategy, including product innovation, customer relationship management, and the use of social media. The results of the research show that Radeva Group has succeeded in increasing market share and customer satisfaction through a marketing approach focused on consumer needs, continuous innovation, and good relationships with vendors and clients. The study also identifies several challenges faced by the company, such as inaccurate information from vendors and sudden demands from clients, and suggests effective solutions to overcome these issues. Based on these findings, the research concludes that adaptive and innovative marketing strategies are essential for the success of companies in the competitive F&B industry.